Guided Into a World Unknown: Reflections on the Making of a Visual Essay With Refugees - van der Maarel, Shirley (Imaginations)

(untitled) (York University, 2022)
The constant presence of refugees in the media has constructed its own reality, at the expense of lived reality. Any work concerned with refugees’ lived experience will need to find ways to encourage people to see beyond this discourse. Based on research with refugees placed in depopulating villages in Italy, this article follows the process of collaboratively creating a visual essay that reflects the lived reality of refugee participants. The essay’s aim is to let readers share in an experience, rather than merely documenting that of others. This article reflects on efforts to achieve this through experimenting with the essay’s form, poetics and aesthetics. In doing so, the article discusses an alternative way of communicating research and presenting a visual essay.